Investigação da β-feniletilamina sobre contratilidade de diferentes órgãos isolados e mecanismo responsável por efeito dual em tiras isoladas de fundo de estômago de ratos - Lima Júnior, Francisco José Batista de (2019)
β-Phenylethylamine (β-PEA) was considered for a long time an indirect sympathomimetic compound. Cloning of trace amine-associated receptors (TAAR) unmasked β-PEA as neurotransmitter, but the role of TAAR in peripheral tissues is yet unsolved. Searching for a response related to a recruitment of TAAR induced by β-PEA, we compared its effects on rat muscle preparations with those typically elicited by the adrenergic agonists phenylephrine or isoproterenol. At lower concentrations, β-PEA relaxed aortic rings previously contracted with phenylephrine in a propranolol-independent manner. In aortic rings under resting tonus, β-PEA induced contraction, effect insensitive to prazosin and observed only at higher β-PEA concentrations. Like phenylephrine, β-PEA induced prazosin-sensitive contractions in spleen strips. In isolated atrium, β-PEA stimulated atrial chronotropism with a lesser potency than isoproterenol but in a propranolol-dependent manner. In tracheal rings, β-PEA induced relaxation not inhibited by propranolol. Under resting tonus, gastric fundus strips contracted in response to β-PEA, an effect that involved extracellular Ca2+ recruitment. Phenylephrine was inert and isoproterenol was relaxant on fundic strips, findings suggestive that β-PEA-elicited contractions did not involve adrenergic receptors. Antagonists of 5-HT receptors, but not EPPTB, a TAAR1 antagonist, inhibited β-PEA-induced contractions on fundic strips. When fundic strips were previously contracted by KCl, β-PEA exerted relaxant effects refractory to 5-HT antagonists, but inhibited by the adenylyl cyclase inhibitor MDL-12,330A.Thus, β-PEA contracted rat gastric fundus with involvement of 5-HT receptors. Under KCl-elicited stimulus, β-PEA-induced relaxation through activation of TAAR1 signalling via the adenylyl cyclase pathway , suggesting a dual role for β-PEA on gastric fundus smooth muscle.